Additional records of the alien gastropod, Ergalatax junionae Houart, 2008 (Gastropoda: Muricidae), from the eastern Mediterranean - KARHAN, S.U.; YOKES, M.B. (Mediterranean Marine Science, 2009)
The alien muricid gastropod Ergalatax junionae Houart, 2008 has been known to inhabit the shallow waters of the eastern Mediterranean. The chronology of its recorded observations, beginning in eastern Turkey and proceeding to the south and west, suggests that it was first introduced to eastern Turkey via shipping, and was then spread in the Levantine Sea. The recent record from Greece indicates that its range of distribution is still expanding. Here we report local population densities and additional records of E. junionae from the eastern Mediterranean basin, including its first occurrence from the Turkish coast of the Aegean Sea.